Population Migration in the Context of Economic Security and Social Stability - L. N. Lipatova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2020)
Target: analysis of migration flows in modern Russia and identification of possible threats to economic security and social stability associated with population migration.Methods: a systematic approach, population analysis, comparative analysis, generalization and interpretation of the results. Results and discussion: On the basis of official statistics and expert estimates, an analysis of the situation in the field of population migration in Russia was carried out, the main directions of population redistribution were identified, the need for adjusting the socio-economic policy in regions experiencing significant migration was substantiated. Conclusions. Conclusions are drawn about the possible increase in the negative impact of migration processes on the socio-economic development of the Russian Federation as a whole and individual regions, in particular, which requires their detailed study in order to take measures to optimize migration flows and adjust social and economic policies.